Lower follicular n-3 polyunsaturated fatty acid levels are associated with a better response to ovarian stimulation - Ruiz-Sanz, José-Ignacio (J Assist Reprod Genet, 2018)
OBJECTIVES: To analyze in detail the fatty acid (FA) composition of follicular fluid (FF) from two-sized follicles at oocyte retrieval and to determine associations of the FAs from large follicles with the woman’s age and the response to ovarian stimulation. DESIGN: Observational study. SETTING: University and fertility clinic. PATIENTS: Sixty-four women (age 19–46), consisting of unfertile patients and oocyte donors, undergoing controlled ovarian stimulation. INTERVENTIONS: None. MAIN OUTCOME MEASURE(S): FF from small (< 12 mm) and large (≥ 18 mm) follicles was collected at oocyte retrieval. FAs by gas chromatography-flame ionization detection. RESULT: Thirty-two FAs with chain lengths ranging from 14 to 25 carbons were identified. There was a readjustment in FA distribution as follicle size increased, raising very long-chain saturated FAs, nervonic (24:1n-9), arachidonic (20:4n-6), and n-3 polyunsaturated FAs (PUFA, P < 0.001), the latter mainly due to an increase in docosahexaenoic acid (22:6n-3, DHA). In large follicles, double bond and peroxidizability indices and total n-3 PUFA, particularly DHA, correlated positively with the woman’s age and negatively with the number of total and mature oocytes, total and top-quality embryos, and fertilization rate. CONCLUSIONS: We have described 32 FAs in ovarian FF, of which 16 changed their distribution with follicle size. The results also indicate that lower n-3 PUFA levels in large follicles, which are associated with younger women, predict a better response to ovarian stimulation based on the recovery of total and mature oocytes, total and top-quality embryos, and fertilization rate per cycle. KEY MESSAGE: The fatty acid profile of ovarian FF changes as the follicle grows and lower n-3 PUFA levels in large follicles, associated with younger women, predict a better response to ovarian stimulation.